b+3/7=b-3/6

Simple and best practice solution for b+3/7=b-3/6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for b+3/7=b-3/6 equation:


b+3/7=b-3/6

We simplify the equation to the form, which is simple to understand
b+3/7=b-3/6

Simplifying:
b + 0.428571428571=b-3/6

Simplifying:
b + 0.428571428571=b-0.5

We move all terms containing b to the left and all other terms to the right.
+1b-1b=-0.5-0.428571428571

We simplify left and right side of the equation.
b=-0.928571428571

0=-0.928571428571

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

See similar equations:

| -21= | | 0.02+0.08=0.04(50+x) | | -9-24=-17 | | 0.15(x+40)-0.04(x-30)=6.1 | | 26+1.3z=9.1 | | 5.2x+17=9.5 | | 3x^2+45=24 | | -35-7n=-7(2n-3) | | 220/5.5= | | x*5+26=x*2+68 | | 5x+3x=7x-1 | | 115+6x=39x+15 | | -8x-(3x+6)=4-5 | | 5t-t-5=3t-6 | | 70-7x=38x+15 | | 0.25(x+60)-0.02(x-20)=20 | | 6x+x-5=6x+7 | | 11-9x=136-44x | | 2(3x+1)-(15-4x)=2x-13 | | 11-9x=7x+17 | | 4x^2=7x-3 | | =a^2-b^2-25-10b | | 3x+1+4x-5=8x-9 | | 5x+3-2x=63 | | -37-9x=7x+17 | | 2x+8=-47-9x | | 9x=126 | | 3x=231 | | 9+5x=41-x | | 5(-4x-7)+10x=17 | | 0.3(x+10)-0.02(x-20)=17.4 | | 11x+5=6x |

Equations solver categories